2011
DOI: 10.1007/s11033-011-0998-5
|View full text |Cite
|
Sign up to set email alerts
|

DNA repair genes polymorphism (XPG and XRCC1) and association of prostate cancer in a north Indian population

Abstract: Prostate cancer is the most commonly diagnosed cancer in men worldwide and is the second leading cause of cancer related mortality. Genetic background may account for the difference in susceptibility of individuals to different diseases and the relationship between genetic polymorphism and some diseases has been extensively studied. There are several common polymorphisms in genes encoding DNA repair enzymes, some of these polymorphisms are reported to result in subtle structural alterations of the repair enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 40 publications
2
33
0
Order By: Relevance
“…Our finding is consistent with those of several other studies in Indian population, American population and African Americans (Hyytinen et al, 1999;Hooker et al, 2008;Berhane et al, 2012). However, the significance of XPG rs2296147 polymorphisms in the development of prostate cancer in Chinese population is unclear.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our finding is consistent with those of several other studies in Indian population, American population and African Americans (Hyytinen et al, 1999;Hooker et al, 2008;Berhane et al, 2012). However, the significance of XPG rs2296147 polymorphisms in the development of prostate cancer in Chinese population is unclear.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have examined the association between DNA repaired gene polymorphisms and risk of prostate cancer in various populations Hooker et al, 2008;Berhane et al, 2012;Liao et al, 2012;Sobti et al, 2012). However, these results are inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“…Three previous studies conducted in Indian, Caucasian-American, and African-American populations, respectively, reported associations between the XPG Asp1104His polymorphism and risk of prostate cancer (Hyytinen et al, 1999;Hooker et al, 2008;Berhane et al, 2012). Our findings strongly indicate that polymorphisms in XPG rs2296147 contribute to prostate cancer susceptibility, which is in line with results of previous studies showing that the XPG rs2296147 TT genotype is associated with increased prostate cancer risk.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings strongly indicate that polymorphisms in XPG rs2296147 contribute to prostate cancer susceptibility, which is in line with results of previous studies showing that the XPG rs2296147 TT genotype is associated with increased prostate cancer risk. Berhane et al (2012) reported that the His/His genotype of XPG was associated with a strongly increased risk of prostate cancer in an Indian population, with an OR of 2.53. Another study conducted in the United States reported that XPG Asp1104His plays an important role in the development of prostate cancer (Hyytinen et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation